2019
DOI: 10.1021/acs.jpcc.9b04258
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Amine-Activated Electrochemical CO2 Conversion with Alkali Salts

Abstract: Amine-based CO 2 chemisorption has been a longstanding motif under development for CO 2 capture applications, but large energy penalties are required to thermally cleave the N-C bond and regenerate CO 2 for subsequent storage or utilization. Instead, it is attractive to be able to directly perform electrochemical reactions on the amine solutions with loaded CO 2. We recently found that such a process is viable in dimethyl sulfoxide (DMSO) if an exogenous Li-based salt is present, leading to formation of CO 2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 51 publications
0
57
0
Order By: Relevance
“…17 Although the catalysts for CO2 electroreduction are selective to reduce CO2 captured by amine-based capture media (RNH2), 17,27,45 the carbamate ions (i.e., RNHCO2) could be the main active reagent for the conversion. 17,46 This is different from the reduction mechanisms in CO2 electrolysis 31 and direct bicarbonate reduction 47,48 . The carbamate ions together with protonated amines (RNH3 + ) are the major products when CO2 is in contact with amines when the CO2 loading is below 0.4 -0.6 mol CO2 per mol amine in the case of 30 % wt.…”
Section: Outlook For Future Integrated Electrolysismentioning
confidence: 84%
See 1 more Smart Citation
“…17 Although the catalysts for CO2 electroreduction are selective to reduce CO2 captured by amine-based capture media (RNH2), 17,27,45 the carbamate ions (i.e., RNHCO2) could be the main active reagent for the conversion. 17,46 This is different from the reduction mechanisms in CO2 electrolysis 31 and direct bicarbonate reduction 47,48 . The carbamate ions together with protonated amines (RNH3 + ) are the major products when CO2 is in contact with amines when the CO2 loading is below 0.4 -0.6 mol CO2 per mol amine in the case of 30 % wt.…”
Section: Outlook For Future Integrated Electrolysismentioning
confidence: 84%
“…Further, including conversion-active cations could weaken the solvent capability to absorb CO2. For instance, Khurram et al 46 reported that including alkali cations such as K + and Cs + could promote direct carbamate reduction but may destabilize the formation of carbamate, which is essential for CO2 absorption. However, the results of our analysis (see Fig.…”
Section: Outlook For Future Integrated Electrolysismentioning
confidence: 99%
“…For example, in DMSO, the inclusion of Lewis acid-alkali cations (Li + , Na + K + ) in EEA solutions substantially increases the proportion of carbamate at the expense of carbamic acid in the solution. This phenomenon has been attributed, via NMR, to electrostatic interactions of the cation with –COO – in the carbamate ( Figure 6 A) ( Khurram et al., 2019 ). The proportion of alkali carbamate with respect to carbamic acid increased strongly with increasing cation Lewis acidity ( Figure 6 B).…”
Section: Special Considerations For Electrochemical Systemsmentioning
confidence: 97%
“… (D) Equilibrium proportion of carbamates from (C). A is adapted and B, C, and D are reproduced with permission from Ref ( Khurram et al., 2019 , 2020 ). Copyright (2019, 2020), American Chemical Society.…”
Section: Special Considerations For Electrochemical Systemsmentioning
confidence: 99%
“…A FE of 72 % for CO was achieved by using an Ag catalyst, at a current density of 50 mA cm À 2 by using 2 M KCl as salt. [58] Adding alkali salts to promote CO 2 conversion from amines was also explored in the same year by Khurram et al [59] In their study, they investigate the role of individual electrolyte salt constituents across multiple cations and anions in DMSO electrolytes to clearly understand the role of these salts in the performance of the reaction. They concluded that although the anion appears to have a minor effect, the cation is found to strongly modulate the thermochemistry of the amine-CO 2 adducts through electrostatic interactions.…”
Section: Co 2 Conversion From Carbamatementioning
confidence: 99%